Lemak Abdominal Ayam Broiler (Gallus sp.) Karena Pengaruh Ekstrak Kunyit (Curcuma domestica Vahl.) - Pratikno, Herry - (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2011)
This research is aimes to know the effect of turmeric extract on broiler abdominal fat. Fourty eight broilerchickens strain CP 707 placed on 48 batteray cages and was randomized, then were acclimated during 1 week.Those chicken was alloted into 4 groups, each group was treated as follows : T0 (control) : were not given turmerinextract; T1 : were given turmerin extract 200 mg/kg BW/day; T2 : were given turmerin extract 400 mg/kg BW/day;T3 : were given turmerin extract 600 mg/kg BW/day. Turmerin extract was given on capsul shape. Replication of thetreatment was 6 times. Long of the treatment was 2 steps, step I (L1) turmerin extract was given during 2-3 weeks (8– 21 days age), step II (L2) the treatment was continued during 3 weeks (22 – 42 days age), turmerin extract dosewas ajusted to the chicken body weight. The chicken were feed with BR I and BR II. Food and drinking water weregiven in an ad libitum manner. Main parameter observed was abdominal fat weight, supporting parameter was bodyweight and food consumption. Data was analyzed by varians analysis with Split Plot Design and continued withDuncan Multiple Range Test. The result was turmerin extract influences broiler’s abdominal fat. Increase anddecrease of abdominal fat are comparable with chicken body weight. On chicken 1 – 4 weeks of age, 200 mg/kgBW/day turmerin extract and 400 mg/kg BW/day turmerin extract increase chicken’s abdominal fat. On chicken 4 –7 weeks of age, 200 mg/kg BW/day turmerin extract increases chicken’s abdominal fat.